FODMAPs, inflammatory bowel disease and gut microbiota: updated overview on the current evidence - Simões, Catarina D. (2022)
Purpose Based on the fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) hypothesis, the low-FODMAP diet has been suggested as a potential therapeutic approach for inflammatory bowel disease (IBD) with promising results on disease management. However, this diet implies a specific broad food restriction, which potentially increases the risk of nutritional deficiencies and may aggravate gut microbiota dysbiosis of IBD patients. The aim of the present study is to review the effect of individual FODMAPs on the human gut microbiota. In addition, this narrative review provides an updated overview of the use of the low-FODMAP diet in IBD, namely the implementation, advantages, limitations, and the impact on the gut microbiota. Methods The literature search strategy was applied to PubMed and Web of Science using relevant keywords, IBD, FODMAPs, Fructose, Lactose, Polyols, FOS, GOS, low-FODMAP diet and gut microbiota. Results Current data suggest that the low-FODMAP diet may effectively improve clinical outcomes in the management of IBD and ensure better quality of life for IBD patients. However, there is evidence highlighting some issues of concern, particularly the adequacy of the diet and the impact on the gut microbiota. The various FODMAP types differently modulate the gut microbiota. Conclusion IBD management should be achieved with the least possible dietary restriction to avoid detrimental consequences, particularly on nutritional adequacy and gut microbiota. Thus, it is important to individualize and monitor the nutrition intervention. Further studies are required to better characterize the relationship between diet, the gut microbiota, and IBD to support the generalization of this approach for clinical practice in IBD therapy and management.